PENGEMBANGAN MODUL EDUKASI KELUARGA ANAK JALANAN DI KAWASAN MALL SKA PEKANBARU - Astuti, Indri Apri; Yakub, Elni; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to develop a family education module for street children. The method used is Research and Development (Research and Development) which is a scientific process for researching, designing, producing, and testing the validity of the products that have been produced. By limiting the steps Sugiyono (2019) used are: (1) Potential and Problems (2) Data collection (3) Product Design (4) Design Validation (5) Design Revision (6) Product Making. The instrument in this study was the validation sheet given to the validator. The validators in this study were 2 BK lecturers, and 2 BK teachers. The results showed that the compilation of street children's family education modules on the Role of Parents in Handling Street Children. The module material consists of (1) Roles, Duties and Functions of the Family, (2) Roles of Good Parenting, (3) Solutions for the Management of Street Children, in terms of material clarity, systematic material, image support, matching the delivery time of the material, completeness Theory. From the value given by the validator, the results obtained from the calculation of the material clarity aspects were obtained with a category of